Analisis Kestabilan Lereng Terhadap Getaran Tanah (Ground Vibration) Akibat Aktivitas Blasting di Pit 10 PT. Alamjaya Bara Pratama Desa Jembayan - Maulana, Risky; Djayus, Djayus; Lepong, Piter (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2020)
This research aims to find out how stable the slopes of the mine are always given ground vibration results from blasting activities. This research was done by estimating the stability of the mine's highwall slope and subsequently given the vibration results from the blasting activity for 30 days using Rocscience SLIDE 6.0 software. The results of this research indicate that the level of ground vibration is too large so that the possibility of landslides on the highwall slopes is very high. So the calculation is done to reducing the amount of ground vibration, one way is to estimate the contents of explosives at a certain distance.